Reformation or exodus: Assessing the future of the Euro. (September 2014) - Watts, Martin; Sharpe, Timothy; Juniper, James
Eurozone economies were the most adversely affected by the Global Financial Crisis, with forecast macroeconomic outcomes still highly uncertain. This article argues first that the Eurozone policy framework can be viewed as neo-liberalism overlaid with policy constraints associated with a mis-specified Optimum Currency Area. We are critical of this framework since it is incompatible with the policy sovereignty that is experienced, if not utilised, by sovereign economies such as the USA, UK and Australia. Second, recent and proposed policy reforms which generally lie within the constraints of the Eurozone framework are examined. We conclude that these policies are piecemeal and fail to restore policy sovereignty, which ultimately requires that member countries exit the Eurozone. Key issues associated with such an exit are briefly discussed.